Distribution and evolution of the LysR-type transcriptional regulators of the Salmonella genus - Dávila S.; Rivera-Ramírez A.; Gama-Martínez Y.; Orozco R.; Hernández V. M.; Hernández-Lucas I. (PLoS ONE, 2026)
LysR-type transcriptional regulators (LTTRs) are one of the most abundant transcriptional regulators in nature and are involved in multiple essential biological process in bacteria. In this work we show that LTTRs are highly abundant in Salmonella enterica subspecies enterica serovars able to infect humans ( S. Typhi), whereas the number of LTTRs decreases substantially in reptile commensals ( Salmonella enterica subspecies arizonae , diarizonae , houtenae , indica, salamae and Salmonella bongori ). In addition, it is also reported the presence of a Salmonella LTTR core, LTTRs exclusive to the Salmonella genus and LTTRs like CysB that is widely distributed in the Enterobacteriales order and their orthologous sequences separate clades at the genus level, suggesting that CysB has evolved in parallel with the corresponding lineage. Therefore, there are LTTRs that evolved as part of the core of microorganisms that provide essential genetic functions to the cell, as well as a LTTR accessory pool that provides different capabilities to specific microorganisms for survival in nature and in different environments of the host.